2021
DOI: 10.1002/ppul.25771
|View full text |Cite
|
Sign up to set email alerts
|

Utility of polysomnography for management of chronic invasive mechanical ventilation in children

Abstract: Objective With advances in technology, pediatric patients are sent home with chronic invasive mechanical ventilation (CIMV). Ventilation optimization and preparation for weaning are essential processes, however, there is no standard approach to weaning and titrating ventilator settings in children. There is little information in the literature on the utility of polysomnography (PSG) in weaning and titration of CIMV. Our objective is to review the role of PSG on titration and weaning of CIMV in children. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Once these children are weaned off the ventilator and continue to improve and thrive, the introduction and demonstration of tolerance for using a speaking valve (Passy Muir) to facilitate swallowing, vocalization, and improved secretion clearance ( 46 , 47 ), followed by tracheostomy tube capping during awake periods, may be prescribed. In our institution, as in many other institutions, to prepare for decannulation, we perform a routine surveillance airway bronchoscopy to look for possible airway obstructive lesions or dynamic airway collapse and a capped overnight sleep study in the sleep lab ( 39 , 43 , 45 , 48 51 ), to ensure successful and safe decannulation. Post decannulation, otolaryngologists and pediatric pulmonologists follow these patients for the management of tracheostomy stoma, other airway complications, and long-term respiratory morbidities related to severe BPD ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once these children are weaned off the ventilator and continue to improve and thrive, the introduction and demonstration of tolerance for using a speaking valve (Passy Muir) to facilitate swallowing, vocalization, and improved secretion clearance ( 46 , 47 ), followed by tracheostomy tube capping during awake periods, may be prescribed. In our institution, as in many other institutions, to prepare for decannulation, we perform a routine surveillance airway bronchoscopy to look for possible airway obstructive lesions or dynamic airway collapse and a capped overnight sleep study in the sleep lab ( 39 , 43 , 45 , 48 51 ), to ensure successful and safe decannulation. Post decannulation, otolaryngologists and pediatric pulmonologists follow these patients for the management of tracheostomy stoma, other airway complications, and long-term respiratory morbidities related to severe BPD ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings showed that contrary to adults where heart failure contributes to central apnea, pediatric patients who have additional underlying conditions such as prematurity or underlying neurologic disorders are at increased risk for central sleep apnea. [37][38][39] Naime et al 40 42 Given the heterogeneous nature of their cohort, more extensive studies are needed to identify which subgroups would benefit most from PSG to assess specific ventilatory needs.…”
Section: Utility Of Polysomnography In Assessing Sleep-disordered Bre...mentioning
confidence: 99%
“…The PSG findings helped with monitoring of clinical status and troubleshooting the ventilator. For the ventilator weaning PSGs, the results obtained informed the decision to wean to lower ventilator settings or off support and keep the patients on the current settings if needed 42 . Given the heterogeneous nature of their cohort, more extensive studies are needed to identify which subgroups would benefit most from PSG to assess specific ventilatory needs.…”
Section: Utility Of Polysomnography In Assessing Sleep‐disordered Bre...mentioning
confidence: 99%
“…Invasive mechanical ventilation (HMV) at home is a revolutionary practice in the care of children with chronic respiratory failure such as neuromuscular diseases, congenital anomalies, or chronic lung diseases. The use of HMV in childhood period has become widespread all over the World 1,2 .…”
Section: Introductionmentioning
confidence: 99%